2012
DOI: 10.1177/1470320312465219
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of aliskiren and valsartan in hypertensive patients with albuminuria: a randomized parallel-group study

Abstract: Introduction: Blockade of the renin-angiotensin system (RAS) is a critical approach to the management of hypertension, especially in proteinuric patients. It is well proven that the direct renin inhibitor aliskiren shows comparable clinical efficacy to the angiotensin II receptor blocker valsartan on blood pressure control and albuminuria. However, there is only limited data on the hand-to-hand effectiveness of these two RAS blockers in improving arterial stiffness. We tested whether aliskiren or valsartan wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
3
0
4
Order By: Relevance
“…These agents offer a cardio-renal protection which may be mediated, at least in part, by their beyond blood pressure control drug-specific effects. In the past, we showed that these agents improve AS and decrease significantly moderately increased albuminuria [36] .…”
Section: Resultsmentioning
confidence: 98%
“…These agents offer a cardio-renal protection which may be mediated, at least in part, by their beyond blood pressure control drug-specific effects. In the past, we showed that these agents improve AS and decrease significantly moderately increased albuminuria [36] .…”
Section: Resultsmentioning
confidence: 98%
“…In total, 40 articles with 53 clinical trials qualified, including 1650 subjects in the ARB treatment group and 1659 subjects in the control. 8,[10][11][12][13] Of all clinical trials, 41 were performed in East Asians, and 12 trials were performed in Caucasians. For the ARB type, 24 trials adopted valsartan, 10 trials adopted telmisartan, 9 trials adopted losartan, 7 trials adopted candesartan and 3 trials adopted irbesartan.…”
Section: Eligible Trialsmentioning
confidence: 99%
“…Several clinical trials explored the potential impact of ARBs on arterial stiffness in various populations. [10][11][12][13] However, a comprehensive evaluation of this impact is lacking. Therefore, we systematically performed a meta-analysis of all published clinical trials that assessed the impact of ARBs on arterial stiffness as measured by PWV compared with other types of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…396,[400][401][402] Από τη σύγκρισή της με άλλους αναστολείς του ΣΡΑΑ έχουν προκύψει αντικρουόμενα αποτελέσματα, καθώς σε 2 μελέτες χαρακτηρίζεται εφάμιλλη της ραμιπρίλης στην ελάττωση της PWV, 396,400 ενώ μια άλλη τη βρίσκει υποδεέστερη της βαλσαρτάνης με το ίδιο κριτήριο. 403 Πρέπει, επίσης, να τονιστεί η πλήρης απουσία δεδομένων σύγκρισης της αλισκιρένης με τα υπόλοιπα αντιυπερτασικά φάρμακα, συμπεριλαμβανομένων των αΜΕΑ, σε σχέση με τα καρδιαγγειακά συμβάματα. Χρήζει, επομένως, διερεύνησης η πιθανή συσχέτιση μεταξύ ωφέλιμης δράσης της αλισκιρένης στην αορτική σκληρία και μείωσης του καρδιαγγειακού κινδύνου.…”
Section: συζητηση -συμπερασματαunclassified
“…Σε μια άλλη μελέτη που συνέκρινε την επλερενόνη με την ατενολόλη για χρονική περίοδο ενός έτους, για ανάλογη ελάττωση της ΑΠενός αΜΕΑ, της ραμιπρίλης, στις ελαστικές ιδιότητες της αορτής, με συγκρίσιμα θετικά αποτελέσματα. 396, 400 Μια άλλη μελέτη σε ασθενείς με ΑΥ και πρωτεϊνουρία, όμως, ανέφερε σημαντικά μεγαλύτερη ελάττωση της PWV από τη βαλσαρτάνη σε σχέση με την αλισκιρένη, παρά τη συγκρίσιμη παράλληλη μείωση τόσο της ΑΥ, όσο και της πρωτεϊνουρίας 403. Ωστόσο, τα υπάρχοντα δεδομένα κρίνονται Ο κλασικός, καρδιοεκλεκτικός, ευρέως χρησιμοποιούμενος για πολλά έτη, βαδρενεργικός αποκλειστής, η ατενολόλη, έχει συσχετιστεί σε πλειάδα μελετών αντιθέτως, αυξήθηκε κατά περίπου 2,5%, ενδεχομένως λόγω της επιβράδυνσης του καρδιακού ρυθμού κατά 8 παλμούς ανά λεπτό 350.…”
unclassified